Application of Quantum Teaching Method to Science Learning Outcomes for Class VI in Elementary Schools: Penerapan Metode Quantum Teaching Terhadap Hasil Belajar IPA Kelas VI di Sekolah Dasar - Yuyun Lestari (Journal of Vocational Education and Information Technology (JVEIT), 2022)
In this study, researchers have examined the shortcomings and obstacles that arise during the teaching and learning process. This is the reason for researchers to apply the quantum teaching method which has been proven to increase student learning outcomes. Based on the results of the study, student learning outcomes have increased significantly. This research went through 2 cycles, namely cycle I and cycle II. In the first cycle, the students' completeness was only 40% and increased in the second cycle to 73.33%. An increase in the average score from 65 in the first cycle to 77.67 in the second cycle, and an increase in the percentage of student learning outcomes, 20% to 77.67 in the first cycle and 33.33% in the second cycle.